2020
DOI: 10.1186/s12885-020-6687-9
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in the sensitivity to crizotinib by Na+/H+ exchanger regulatory factor 1 is dependent to its subcellular localization in ALK-positive lung cancers

Abstract: Background: Na + /H + exchanger regulatory factor 1 (NHERF1) is an important scaffold protein participates in the modulation of a variety of intracellular signal pathways. NHERF1 was able to enhance the effects of chemo-drugs in breast and cervical cancer cells. Anaplastic lymphoma kinase (ALK) fusion mutations are validated molecules targeted therapy in lung cancers, where crizotinib can be used as the specific inhibitor to suppress tumor progression. However, due to the less frequent occurrence of ALK mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Crizotinib induces anticancer activity in human cervical cancer cells through ROS-dependent mitochondrial depolarization and induction of apoptosis pathways ( Varma and Tiwari, 2021 ). In addition, the sensitivity of crizotinib could be enhanced by Na+/H+ exchanger regulator factor 1 (NHERFI) ( Yang et al, 2020 ). Our current study also showed cervical cancer patients in low-risk groups were more sensitivity to crizotinib.…”
Section: Discussionmentioning
confidence: 99%
“…Crizotinib induces anticancer activity in human cervical cancer cells through ROS-dependent mitochondrial depolarization and induction of apoptosis pathways ( Varma and Tiwari, 2021 ). In addition, the sensitivity of crizotinib could be enhanced by Na+/H+ exchanger regulator factor 1 (NHERFI) ( Yang et al, 2020 ). Our current study also showed cervical cancer patients in low-risk groups were more sensitivity to crizotinib.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear and cytoplasmic extracts of cells were prepared using nuclear and cytosol extraction kit from Applygen, as earlier described [ 25 ]. Whole-cell extracts were prepared by lysing the cells in ice-cold CEB-A buffer (Applygen Technologies Inc., Beijing, China).…”
Section: Methodsmentioning
confidence: 99%
“…The expression and regulation of NHERF1 have been comprehensively studied in various tumors (breast, colon, uterine cervix, etc. ), as well as its possible role on the effects of chemotherapeutic drugs ( 18 , 19 ). The results showed emerging evidence of altered expression associated with tumor behavior.…”
Section: Introductionmentioning
confidence: 99%